THE IMPLEMENTATION OF IRONY OF THE OLD MAN AS INDICATED ON LUIGI PIRANDELLO'S WAR - Putri Ayu Millenia; Nia Ayu Fitriani; Rindrah Kartiningsih; Rommel Utungga Pasopati (Jurnal Sosial Humaniora dan Pendidikan, 2023)
Irony is an act to say something other than literal meaning. Somehow, it is used to cover up the sadness experienced. The old man is a character in a short story entitled War written by Luigi Pirandello. In a conversation in the Night Express, so many people talked about their sadness that nothing could cheer them up. Then, an old man came and told them that they should not be sad for their son who died. Actually, the old man feels the same sadness but he would never want to show it off to others. Then, how is the implementation of irony of the old man indicated on Luigi Pirandello’s War? Through qualitative method, this writing underlines irony as the way the old man covered the sadness he experienced when he lost his son. Supported by theory of Ronald Tanaka, the implementation of the irony of the old man is seen when he spoke a lot to cover his grief. He said that their sons are on their own and belong to the state when they grew up. Then, they should also be proud of their son because they are the heroes of country. In conclusion, the old man covered up his sadness by complimenting others’ son. Meanwhile, the irony is his son as a hero is also included in his saying.